Block Format Instruction. Final Report - Kenner, Morton R.; Stephens Coll., Columbia, MO. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1970)
Reported is a study of the use of instructional blocks in college freshman mathematics courses. The first year of the project, one course was organized to have three large group lectures per week and one small group tutorial session per week. In addition, help sessions were made available. Problem materials were developed in connection with text materials and a computer laboratory was used. During the second year, four courses were involved; one with programed texts and which met every day; three with the same format as before. Evaluation of results indicates significant reduction in staff cost per student and discovery of topics and media for future study. The instructional pattern will receive further evaluation. Appendices include: a mathematics diagnostic test, sample tutorial problems, sample of a computer program, teacher evaluation questionnaire, and sample journal articles for tutorials. (JG)
Sponsoring Agency: Office of Education (DHEW), Washington, DC. Bureau of Research.
Contract Number: OEG-6-9-008040-0037(057).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Freshmen; College Mathematics; Instruction; Programed Instructional Materials; Research; Teaching Methods